SYNTHESIS AND CHARACTERIZATION OF SOME METAL COMPLEXES WITH IEA AS LIGAND DERIVED FROM 2-ACETLYLINDAN-1,3-DIONE - Kumar, Devesh; Singh, Vipin Kumar (Journal of Drug Delivery and Therapeutics, 2014)
The present investigation are based on the synthesis and characterization of metal complexes with Schiff’s bases (anils) Indeno–ethylidene aniline (C17H13O2N), (IEA), (L1H) derived from 2-substituted acetyl 1, 3 - dione by condensing it with primary aryl amine (aniline) in absolute alcohol. The Co (II), Ni(II), Cu (II), Zn (II), Cd (II), Fe (III), V (III) and Cr (III) complexes of the Schiff’s bases have been prepared in the reactions and investigated their structures by physicodemical methods. The formulation and structure of the ligands have been screened by their chemical analysis, IR, PMR and mass-spectral studies. The structure of the anils has been characterized by their IR spectra which showed strong absorption at 1705, 1650 and 1570 cm-1 along with other bands. The structure of ligand has been confirmed by their mass–spectral studies. Keywords: Metal Complexes, Schiff’s bases, 2-Acetlylindan-1,3-Dione